Analysis Of Factors Affecting Nurse Work Stress At Daha Husada General Hospital Kediri City In 2021 - Afelina Krissinta Rahayu Putri; Prima Dewi Kusumawati (Universitas STRADA Indonesia, 2022)
As explained in Article 1 of Law No. 13 of 2003 on Employment, Labor is any person who is able to work to produce goods and/or services to meet their own needs and serve the community. According to (International Labour Organization, 2016), long working hours pose a risk to the health and safety of workers and affect a person's work stress. The design of this study used a cross sectional method in which the measurement of work stress and workload factors, conflict, responsibility, facilities and infrastructure as well as working hours that affect it is done simultaneously or at one time. This study has a population of 79 people, conducted with a quantitative approach, sampling techniques using simple random sampling and Ordinal regression analysis.This study found that there is a variable effect of workload on nurses 'work stress with a value of sig 0.036 and there is a variable effect of conflict with nurses' work stress with a value of sig 0.001. While the responsibility variable has no influence on the work stress of nurses with a value of sig 0.628, variable facilities and infrastructure has no influence on the work stress of nurses with a value of sig 0.099 and variable working hours have no influence on the work stress of nurses with a value of sig 0.288. It can be concluded that there is an influence of workload and conflict factors on the work stress of nurses at Daha Husada General Hospital Kediri. While there are 3 variables that do not affect the responsibility, facilities and infrastructure as well as working hours to work stress nurses at the hospital daha Husada Kediri. As explained in Article 1 of Law No. 13 of 2003 on Employment, Labor is any person who is able to work to produce goods and/or services to meet their own needs and serve the community. According to (International Labour Organization, 2016), long working hours pose a risk to the health and safety of workers and affect a person's work stress. The design of this study used a cross sectional method in which the measurement of work stress and workload factors, conflict, responsibility, facilities and infrastructure as well as working hours that affect it is done simultaneously or at one time. This study has a population of 79 people, conducted with a quantitative approach, sampling techniques using simple random sampling and Ordinal regression analysis.This study found that there is a variable effect of workload on nurses 'work stress with a value of sig 0.036 and there is a variable effect of conflict with nurses' work stress with a value of sig 0.001. While the responsibility variable has no influence on the work stress of nurses with a value of sig 0.628, variable facilities and infrastructure has no influence on the work stress of nurses with a value of sig 0.099 and variable working hours have no influence on the work stress of nurses with a value of sig 0.288. It can be concluded that there is an influence of workload and conflict factors on the work stress of nurses at Daha Husada General Hospital Kediri. While there are 3 variables that do not affect the responsibility, facilities and infrastructure as well as working hours to work stress nurses at the hospital daha Husada Kediri.